Photoelectrochemical properties of electrochemically deposited CdIn2S4 thin films - Kokate, A. V.; Asabe, M. R.; Delekar, S. D.; Gavali, L. V.; Mulla, Imtiaz S.; Hankare, P. P.; Chougule, B. K. (Journal of Physics and Chemistry of Solids, 2006)
Thin films of CdIn2S4 have been deposited on to stainless steel and fluorine-doped tin oxide (FTO)-coated glass substrates from aqueous acidic bath using an electrodeposition technique. Ethylene diamine tetra-acetic acid (EDTA) disodium salt is used as complexing agent to obtain good-quality deposits by controlling the rate of the reaction. The different preparative parameters like concentration of bath, deposition time, bath temperature, pH of the bath have been optimized by the photoelectrochemical (PEC) technique in order to get good-quality photosensitive material. Different techniques have been used to characterize CdIn2S4 thin films. Optical absorption shows the presence of direct transition with band gap energy 2.17 eV. The X-ray diffraction (XRD) analysis of the as-deposited and annealed films showed the presence of polycrystalline nature. Energy-dispersive analysis by X-ray (EDAX) study for the sample deposited at optimized preparative parameters shows that the In-to-Cd ratio is almost 2 and S-to-Cd ratio is almost 4. Scanning electron microscopy (SEM) for samples deposited at optimized preparative parameters reveals that spherical grains are uniformly distributed over the surface of the substrate indicates the well-defined growth of polycrystalline CdIn2S4 thin film. PEC characterization of the films is carried out by studying photoresponse, spectral response and photovoltaic output characteristics. The fill factor (ff) and power conversion efficiency (eta) of the cell are 69 and 2.94%, respectively. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Thin films; X-ray diffraction

Monitoring structural defects and crystallinity of carbon nanotubes in thin films - Mahajan, S. S.; Bambole, M. D.; Gokhale, S. P.; Gaikwad, A. B. (Pramana-Journal of Physics, 2010)
We report the influence of catalyst formulation and reaction temperature on the formation of carbon nanotube (CNT) thin films by the chemical vapour deposition (CVD) method. Thin films of CNTs were grown on Fe-Mo/Al(2)O(3)-coated silicon wafer by thermal decomposition of methane at different temperatures ranging from 800 to 1000A degrees C. The electron microscopic investigations, SEM as well as HRTEM, of the as-grown CNT thin films revealed the growth of uniform multi-walled CNTs in abundance. The intensity ratio of D-band to G-band and FWHM of G-band through Raman measurements clearly indicated the dependency of structural defects and crystallinity of CNTs in thin films on the catalyst formulation and CVD growth temperature. The results suggest that thin films of multi-walled CNTs with negligible amount of defects in the nanotube structure and very high crystallinity can be obtained by thermal CVD process at 925A degrees C.
Keywords: Carbon nanotubes; chemical vapour deposition; Raman spectroscopy; scanning electron microscopy; Thin films

Preparation and characterization of CuInSe2 thin films by chemical bath deposition technique - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2010)
Copper indium diselenide (CIS) thin films have been deposited using a precursor solution containing copper sulphate, indium trichoride, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium at room temperature. The as grown brown colored films were found to be well adherent to glass substrates. The films were characterized by X-ray diffraction, scanning electron microscopy, atomic absorption spectroscopy, optical absorption, electrical resistivity, and thermo electric measurement techniques. The analysis of optical absorption data shows band-gap energy (E-g) to be 1.1 eV. The electrical resistivity of the thin film was found to be of the order of 10(2) (Omega cm). Thermoelectric power measurement shows n-type conduction. (C) 2010 Published by Elsevier B.V.
Keywords: CuInSe2; Optical properties; Thin films; X-ray diffraction

Synthesis and characterization of nickel selenide thin films deposited by chemical method - Hankare, P. P.; Jadhav, B. V.; Garadkar, K. M.; Chate, P. A.; Mulla, Imtiaz S.; Delekar, S. D. (Journal of Alloys and Compounds, 2010)
Nickel selenide thin films have been deposited using chemical bath method on non-conducting glass substrates in a tartarate bath containing nickel sulphate octahydrate, hydrazine hydrate, sodium seleno-sulphate in an aqueous alkaline medium. The grown films were uniform, well adherent and black in color. The films were characterized using X-ray diffraction, scanning electron microscopy, optical absorption and electrical measurements. The nickel selenide thin film revealed polycrystalline nature with hexagonal system. The direct optical band gap of the film was found to be 1.61 eV. Electrical resistivity of film was observed in the order of 10(3) (Omega cm) with p-type conduction mechanism. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Semiconductors; Thin films; X-ray diffraction

Vanadia-titania thin films for photocatalytic degradation of formaldehyde in sunlight - Akbarzadeh, Rokhsareh; Shubhangi B. Umbarkar; Sonawane, Ravindra S.; Takle, Srikant; Dongare, Mohan K. (Applied Catalysis A-General, 2010)
Thin films of vanadia-titania with good adhesion to the substrates have been deposited on various substrates such as glass slides, glass helix and silica raschig rings by simple sol-gel dip coating process using vanadium and titanium peroxide gel. The optimum concentration of vanadia in titania for obtaining good uniform viscous gel was found to be 0.5-4 wt% beyond which the vanadia particles disturb the gel network, resulting in the formation of a gelatinous precipitate. The films of vanadia-titania as well as the dried powder of the bulk gel were characterized by different characterization techniques. Optical characterization by UV-vis spectrophotometer showed a shift in optical absorption wavelength to the visible region that may be due to the incorporation of vanadia into titania structure. The XRD revealed the formation of anatase phase in pure titania as well as titania with up to 2% vanadia loading, whereas formation of rutile as minor phase along with anatase as major phase was observed at higher vanadia loading. The XRD did not show any peaks of vanadia phase up to 5% vanadia loading indicating either incorporation of vanadia into titania structure or high dispersion of amorphous vanadia on titania support. The pure and vanadia doped TiO(2) thin films were evaluated for their photocatalytic activity for degradation of methylene blue as a model pollutant under sunlight. Doping Of V(2)O(5) in TiO(2) showed an increase in the photo-degradation rate of methylene blue by a factor of 3-6.6 times compared to pure TiO(2). The highest rate has been obtained for 4% V(2)O(5)-doped TiO(2) films. Vanadia doped TiO(2) thin films were also found to be very active for photocatalytic degradation of formaldehyde from aqueous solution in sunlight. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Formaldehyde; Methylene blue; Photocatalysis; Sunlight; Thin films; V(2)O(5)/TiO(2)

Enhanced dielectric permittivity in poly (vinylidene) fluoride/multiwalled carbon nanotubes nanocomposite thin films fabricated by pulsed laser deposition - Chanmal, Chetan; Deo, Meenal S.; Jog, Jyoti Prakash (Applied Surface Science, 2011)
The fabrication of high quality thin films of poly (vinylidene fluoride) embedded with multiwalled carbon nanotubes using pulsed laser deposition technique is reported. The prepared films were characterized for structural, morphology and dielectric properties. The morphology analysis revealed uniform dispersion of multiwalled carbon nanotubes throughout the polymer matrix. X-ray diffraction results suggested that the poly (vinylidene fluoride) film is in amorphous phase while addition of multiwalled carbon nanotubes showed presence of crystalline peaks in the nanocomposites films. It was interesting to note that the nanocomposite films exhibits significant enhancement of the ferroelectric beta-phase as evidenced by the X-ray diffraction and Fourier transform infrared spectroscopy results. The dielectric analysis shows a remarkable enhancement in the dielectric permittivity of nanocomposites with lower loss and conductivity level. The results can be attributed to the formation of minicapacitor network and relatively higher percolation threshold in the nanocomposites. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dielectric permittivity; Ferroelectric polymer; Percolation threshold; pulsed laser deposition; Thin films

Low thermal emissive surface properties of ZnO/polyimide composites prepared by pulsed laser deposition - Babrekar, Harshada A.; Jejurikar, S. M.; Jog, Jyoti Prakash; Adhi, K. P.; Bhoraskar, S. V. (Applied Surface Science, 2011)
We report the low thermal-emissive surface properties of composites of ZnO-polyimide. The composites were synthesized by depositing ZnO on polyimide surface by pulsed laser deposition technique. ZnO target was ablated at different incident energy densities and the substrate (polyimide) was held at elevated temperature. This facilitated the c-axis oriented growth of ZnO, which was inferred from the X-ray diffraction analysis. The composites consisted of multilayers having different electrical resistivities. The values of which are also estimated from Hagen-Rubens relation. The reduced infrared emissivities of the composite films, as compared to polyimide, were correlated to the increased carrier concentration and reduced surface resistivity estimated from the Hall measurements. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: pulsed laser deposition; Thermal emissivity; Thin films; Zinc oxide

One-step in situ synthesis of NHx-adsorbed rhodium nanocrystals at liquid-liquid interfaces for possible electrocatalytic applications - Patil, V. S.; Krishna, S. R.; Hawaldar, Ranjit R.; Gaikwad, A. B.; Sathaye, S. D.; Patil, K. R. (Journal of Colloid and Interface Science, 2011)
Nearly monodisperse rhodium nanoparticles with adsorbed NHx were synthesized at the CCl4-water interface. The presence of NHx-adsorbed species was confirmed by energy-dispersive X-ray analysis (EDX) and X-ray photoelectron spectroscopy (XPS) studies. The synthesis of controlled size 2-38 nm rhodium particles was studied as a function of reducing agent concentration by transmission electron microscopy (TEM). HRTEM confirmed the formation of rhodium nanoparticles having fringe spacing consistent with reported Rh (1 1 1) planes. The continuity of these films over an area of 1 x 1 pm was revealed by atomic force microscopy (AFM) studies. The electrocatalytic application of these nanostructure Rh-NHx), thin films for formaldehyde oxidation in 0.5 M NaOH was investigated by cyclic voltammetry. The Rh nanoparticles formed by the present strategy are expected to be useful for other catalytic applications also. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Hydrazine hydrate; Liquid-liquid interface; Nanoparticles; Rhodium; Thin films

Effect of the surface roughness of conducting polypyrrole thin-film electrodes on the electrocatalytic reduction of nitrobenzene - Adhikari, Arindam; Radhakrishnan, S.; Vijayan, M. (Journal of Applied Polymer Science, 2012)
Conducting polypyrrole (PPy) thin-film electrodes were prepared by the electropolymerization of pyrrole on gold-coated glass plates. Films of various roughnesses were obtained by the variation of the scan rates during electropolymerization. These thin films were modified by doping with 6mM of the dopant NiCl2. The surface morphology of the films was studied by scanning electron microscopy and atomic force microscopy (AFM), which suggested films prepared with a high scan rate were rougher in nature than the films produced with a low scan rate. The electrocatalytic reduction of nitrobenzene was carried out with these electrodes with the cyclic voltammetry technique in acetonitrile containing 0.1M HClO4 as a supporting electrolyte. The various results obtained show that the conducting PPy thin-film electrodes were catalytically active toward the electroreduction process. The modified PPy film electrodes doped with NiCl2 were more active toward nitrobenzene electroreduction than the PPy film alone. The results indicate that the roughness of the films played a very important role in determining their catalytic activity. The PPy films that were more rough in nature were catalytically more active than the smooth films; this may have been due to the availability of more reactive sites in the case of rough films. The apparent diffusion coefficients of the PPy film electrodes were also calculated. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: atomic force microscopy (AFM); conducting polymers; Diffusion; surface modification; Thin films

Synthesis and X-ray single crystal structure of a cadmium(II) acetophenone thiosemicarbazone complex and its use as a single-source precursor for the preparation of CdS nanocrystallites and thin films - Palve, Anil M.; Joshi, Pranaya V.; Puranik, Vedavati G.; Garje, Shivram S. (Polyhedron, 2013)
{A cadmium(II) acetophenone thiosemicarbazone complex has been prepared and characterized by elemental analysis, infrared and nuclear magnetic resonance (H-1 and C-13H-1) spectroscopic techniques. Its single crystal structure has also been determined. The compound is found to be monoclinic, space group C2/c, with a = 12.1020(3) angstrom
Keywords: CdS; Nanocrystallites; Single source precursor; Thin films; Thiosemicarbazone complex

Poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite based thin films for Schottky diode application - Gupta, Bhavana; Mehta, Minisha; Melvin, Ambrose A.; Kamalakannan, R.; Dash, Sitaram; Kamruddin, M.; Tyagi, A. K. (Materials Chemistry and Physics, 2014)
Transparent, conductive films of poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite were synthesized by in-situ oxidative polymerization and investigated for their Schottky diode property. The prepared films were characterized by UV-Vis spectroscopy, thermal gravimetric analysis (TGA), surface resistivity, cyclic voltametery, scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). SEM reveals the formation of homogeneous and adhesive polymer films while HRTEM confirms the uniform wrapping of polymer chains around the nanotube walls for PEDOT-FWCNT film. Improved thermal stability, conductivity and charge storage property of PEDOT in the presence of FWCNT is observed. Among different compositions, 5 wt. % of FWCNT is found to be optimum with sheet resistance and transmittance of 500 Omega sq(-1) and 77%, respectively. Moreover, the electronic and junction properties of polymer films were studied and compared by fabricating sandwich type devices with a configuration of Al/PEDOT or PEDOT-FWCNT nanocomposite/indium tin oxide (ITO) coated glass. The measured current density-voltage characteristics show typical rectifying behavior for both configurations. However, enhanced rectification ratio and higher forward current density is observed in case of PEDOT-FWCNT based Schottky diode. Furthermore, reliability test depicts smaller hysteresis effect and better performance of PEDOT-FWCNT based diodes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Composite materials; Electrical properties; Polymer; Thin films

Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

Gold incorporated mesoporous silica thin film model surface as a robust SERS and catalytically active substrate - Sekhar, Anandakumari Chandrasekharan Sunil; Vinod, Chathakudath Prabhakaran (Molecules, 2016)
Ultra-small gold nanoparticles incorporated in mesoporous silica thin films with accessible pore channels perpendicular to the substrate are prepared by a modified sol-gel method. The simple and easy spin coating technique is applied here to make homogeneous thin films. The surface characterization using FESEM shows crack-free films with a perpendicular pore arrangement. The applicability of these thin films as catalysts as well as a robust SERS active substrate for model catalysis study is tested. Compared to bare silica film our gold incorporated silica, GSM-23F gave an enhancement factor of 10(3) for RhB with a laser source 633 nm. The reduction reaction of p-nitrophenol with sodium borohydride from our thin films shows a decrease in peak intensity corresponding to -NO2 group as time proceeds, confirming the catalytic activity. Such model surfaces can potentially bridge the material gap between a real catalytic system and surface science studies.
Keywords: gold nanoparticles; model catalysis; SERS; Thin films

Extraction of the very high tunneling current and extremely stable emission current from GdB6/W-tip source synthesized using arc plasma - Suryawanshi, Sachin R.; Kanhe, Nilesh; Mathe, Vikas L.; Phase, Deodatta M.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Herein, we report the one step arc plasma synthesis of the GdB6 (Gadolinium hexaboride) nanoparticles and its field emission (FE) characteristics on tungsten point substrate (GdB6/ W). The SEM /TEM analysis revealed the GdB6 nanoparticles on W point substrate exhibit irregular shaped, grainy, dense, course morphology, i.e. uniformly covering the entire tip substrate surface. For GdB6/W point source, the values of the turn-on and threshold fields, defined as field required to draw an emission current density similar to 1 mA/cm(2) and similar to 100 mA/cm(2), respectively are found to be similar to 2.2 and similar to 2.7 V/mm, for anodecathode separation of similar to 1 mm. Interestingly, a very high emission current density of similar to 3.5 A/cm(2) has been drawn from the GdB6/W point emitter at relatively lower applied field of similar to 6.4 V/mm. The field enhancement factor found to be similar to 10,250. The GdB6/W point electron source exhibits a good emission current stability at similar to 10 mA for a period of 6 hr. The emission current stability is enumerated in terms of standard deviation and its magnitude has been measured to be only 1.72% with respect to the average value. The superlative field emission characteristics signify the GdB6/W point electron source as potential candidates for vacuum micro/nanoelectronics device applications.
Keywords: Arc Plasma; field emission; Thin films

Surface modification of polymers for tissue engineering applications: arginine acts as a sticky protein equivalent for viable cell accommodation - Sengupta, Poulomi (ACS Omega, 2018)
Hydrophobic polymers, for their favorable mechanical properties, are a popular choice as permanent bioimplants. These materials remain absolutely bioinert for years, but throw up challenges when it comes to fast integration with healthy tissue. Addressing this, herein, we present a surface-modification technique of converting the hydrophobic surface of a polymeric film into a hydrophilic one using a layer-by-layer assembly process involving gold nanoparticles and small molecules like amino acids. These films showed much improved animal cell (murine fibroblast) adherence properties compared to commercially available tissue culture plates. Moreover, arginine-modified films exhibited a nearly equivalent cell viability compared to the films modified with the natural extracellular matrix component fibronectin. The surface hydrophilicity and roughness of our novel film were characterized by contact angle measurement and atomic force microscopy. Cell counting, fluorescence microscopy, cell viability, and collagen estimation assay were employed to demonstrate that our film favored a much improved cell adherence, and accommodation in comparison to the commercially available tissue culture plates.
Keywords: Cell and Molecular biology; Extracellular matrix proteins; Nanoparticles; Physical and chemical properties; Polymers; Proteins; Surface structure; Surface treatment; Thin films; tissue engineering

Sustainable UV absorbing bio-plastic films by valorisation of humins and chitosan - Lucas, Nishita; Tambe, Snehal S.; Parate, Roopa; Hengne, Amol; Rode, C. V.; Athawale, Anjali A. (International Journal of Biological Macromolecules, 2025)
Humins, an inevitable bio-refinery waste by-product of sugar dehydration have been efficiently utilized for the first time for developing biodegradable thin films for UV shielding. The films were prepared from chitosan, and humins, a novel combination, aiming towards simultaneous utilization of marine and bio-refinery waste, rendering simple, effective, robust UV absorbing films. The structure-activity relationship of these films were elucidated with the help of different analytical techniques like X-ray diffraction, Fourier transform infrared spectroscopy, Thermogravimetric analysis, UV-vis spectroscopy, Atomic force microscopy, Scanning electron microscopy, Tensile testing, Contact angle measurements and water absorption studies. Intrinsic biodegradability was studied using fungi i.e. Aspergillus niger. Different feedstocks (corncob, rice husk, glucose and xylose) were explored for generating humins. Amongst them, humins derived from xylose were utilized for the preparation of the bio-plastic films of chitosan. The results revealed that, addition of 5.0 % humins was observed to be an optimum concentration yielding films with excellent UV absorption, mechanical properties, and biodegradability. The current work is in perfect alignment with sustainability and green chemistry as it ameliorates waste valorization (lignocellulosic and marine altogether). Further, its innovation stems from the first-hand use of humins for UV absorption, novel combination of biopolymers, use of green raw materials.
Keywords: biodegradable; Chitosan; Humins; Thin films; UV absorption; Waste valorization